2010
DOI: 10.1158/0008-5472.can-09-2982
|View full text |Cite
|
Sign up to set email alerts
|

Local Radiation Therapy Inhibits Tumor Growth through the Generation of Tumor-Specific CTL: Its Potentiation by Combination with Th1 Cell Therapy

Abstract: Radiation therapy is one of the primary treatment modalities for cancer along with chemotherapy and surgical therapy. The main mechanism of the tumor reduction after irradiation has been considered to be damage to the tumor DNA. However, we found that tumor-specific CTL, which were induced in the draining lymph nodes (DLN) and tumor tissue of tumor-bearing mice, play a crucial role in the inhibition of tumor growth by radiation. Indeed, the therapeutic effect of irradiation was almost completely abolished in t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
173
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 212 publications
(181 citation statements)
references
References 37 publications
7
173
1
Order By: Relevance
“…The antitumor activity of cytotoxic T cells can be observed in the non-irradiated field. Such Abscopal responses can be achieved by irradiating either primary or metastatic tumors [13][14][15][16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…The antitumor activity of cytotoxic T cells can be observed in the non-irradiated field. Such Abscopal responses can be achieved by irradiating either primary or metastatic tumors [13][14][15][16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, this may become a promising tool for developing TCR gene immunotherapy. We recently demonstrated that introducing Th1-dominant immunity is essential for inducing fully activated CTLs and immunological memory in tumor-bearing hosts (9,18,19,30). It has also been demonstrated that a mixture of various synthetic long peptides derived from naturally occurring sequences of HPV-16 oncoproteins was superior to short tumor peptides in terms of inducing complete or partial response in vulvar intraepithelial neoplasia (12).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, it is widely accepted that inflammatory cells, which are present in the tumor microenvironment, and the tumor immune response, which is activated by ionizing radiation, significantly affect tumor development (28)(29)(30)(31). This tumor-generated inflammatory response may result in an increased propensity for apoptosis, angiogenesis and DNA damage by upregulating cytokines and inflammatory mediators.…”
Section: Introductionmentioning
confidence: 99%